2021
DOI: 10.21203/rs.3.rs-689481/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting Inter-individual Variability in Endoxifen Concentrations in Patients: Results From the Prospective TOTAM Trial

Abstract: Introduction: Endoxifen – the principal metabolite of tamoxifen – is subject to a high inter-individual variability in serum concentration. Numerous attempts have been made to explain this, but thus far only with limited success. By applying predictive modelling, we aimed to identify factors that determine the inter-individual variability. Aim is to develop a prediction model for endoxifen concentrations, as a strategy to individualize tamoxifen treatment by model-informed dosing in order to prevent subtherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A previous study showed similar results where both age and weight were statistically significant predictors, but only explained a small percent (1.5-1.8%) of the total variability with small effect sizes after adjusting for CYP2D6 genotype, respectively. 42 Additionally, a prospective, multicenter study on 1977 patients with breast cancer taking adjuvant TAM, observed decreased END concentrations in older patients reflecting age effect on TAM metabolic ratio. 43 A suggested explanation is an expected reduction in older patients of the enzymatic activity causing the lower formation of END.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed similar results where both age and weight were statistically significant predictors, but only explained a small percent (1.5-1.8%) of the total variability with small effect sizes after adjusting for CYP2D6 genotype, respectively. 42 Additionally, a prospective, multicenter study on 1977 patients with breast cancer taking adjuvant TAM, observed decreased END concentrations in older patients reflecting age effect on TAM metabolic ratio. 43 A suggested explanation is an expected reduction in older patients of the enzymatic activity causing the lower formation of END.…”
Section: Discussionmentioning
confidence: 99%